Effect of integrated nutrient management on growth and quality traits of lettuce (Lactuca sativa) - NATH, KANGKANA; SARMA, IRA; GOGOI, SAILEN; BORAH, NILAY; KALITA, PRAKASH; DAS, REECHA T (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at the research farm of Assam Agricultural University, Jorhat, Assam during winter (rabi) seasons of 2019–20 and 2020–21 to study the effect of integrated nutrient management on growth and quality of lettuce (Lactuca sativa L.). The experiment was laid out in a randomized block design (RBD) with eight treatments and three replications. The treatment combinations were T1, Control; T2, 40:20:40 NPK kg/ha; T3, 40:20:40 NPK kg/ha + FYM 2 tonnes/ha; T4, 40:20:40 NPK kg/ha + FYM 2 tonnes/ha + PSB; T5, FYM 3 tonnes/ha + PSB; T6, 40:20:40 NPK kg/ha +VC 1 tonnes/ha; T7, 40:20:40 NPK kg/ha + VC 1 tonnes/ha + PSB and; T8, VC 2 tonnes/ha + PSB. Observations on the growth parameters were taken at 30 DAP, 45 DAP and at harvest. Among the treatments, T7 recorded the highest yield (27.5 tonnes/ha), net income (192703.00) and other quality parameters. However, the benefit-cost ratio was found maximum (2.6) in the treatment T4 due to lesser cost of FYM as compared to vermicompost used in the treatment T7. Therefore, the combined use of NPK, FYM and PSB (T4) may be recommended for economic as well as environment friendly production of lettuce.